2019
DOI: 10.1111/aec.12712
|View full text |Cite
|
Sign up to set email alerts
|

Ant community patterns in highly fragmented Chaco forests of central Argentina

Abstract: The Chaco is the largest dry forest biome in South America and one of the regions most threatened by agricultural intensification. As a consequence, in several areas Chaco forests persist as forest remnants of different sizes embedded in an agricultural matrix. Ants are social insects that have key roles in ecosystem functioning, and the effects of this ongoing land use change process on ant communities are little known for this region. In the present study, we assessed the consequences of land use replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Our findings are in line with Pereyra et al (2019), who suggested that even small forest fragments could have an important value for the conservation of ants. Ross et al (2018) found no detrimental effect of habitat fragmentation on ant diversity, although habitat fragment size was correlated with estimated species richness.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with Pereyra et al (2019), who suggested that even small forest fragments could have an important value for the conservation of ants. Ross et al (2018) found no detrimental effect of habitat fragmentation on ant diversity, although habitat fragment size was correlated with estimated species richness.…”
Section: Discussionsupporting
confidence: 93%
“…The invasive ant W. auropunctata and the South American big-head ant P. obscurithorax (another known native ant species also invasive in the United States) were very common and indicator species of the Chaco forest. Interestingly, W. auropunctata was present, together with Brachymyrmex patagonicus Mayr, 1868 (another well-known invader), in all the Chaco forest fragments studied by Pereyra et al (2019), independently of fragment size and isolation, indicating that their dispersal is not limited in this context of land-use change. This species is considered as a disturbed habitat indicator because it is strongly associated with fragmented dry tropical forest edges in Brazil and Colombia (Majer & Delabie, 1999;Achury et al, 2008Achury et al, , 2012 and disturbed habitats both within its native and introduced range (Foucaud et al, 2009;Orivel et al, 2009;Chifflet et al, 2018).…”
Section: Implications For Conservationmentioning
confidence: 96%
“…Also, insects belonging to different taxa respond differentially to fragmentation. Additionally, fragmentation facilitates alien insects that can disrupt native insect diversity and community structure (Pereyra et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fragmentation facilitates alien insects that can disrupt native insect diversity and community structure (Pereyra et al, 2019).…”
Section: Introductionmentioning
confidence: 99%